Strategi Pemasaran Dan Kualitas Pelayanan Dalam Meningkatkan Kepuasan Dan Loyalitas Pelanggan Bank BJB - Elvira Aprilia Primastika; R Yuniardi Rusdianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
. Bank BJB is a banking industry operating under the auspices of the Regional-Owned Enterprises located in West Java. The purpose of this research is to determine the influence of marketing strategies and service quality on customer satisfaction and loyalty at Bank BJB Branch Office in Mojokerto. This research uses a qualitative method with data obtained from interviews, observations, and documentation. The results of the study indicate that marketing strategies and service quality have a significant impact on customer satisfaction and loyalty, as evidenced by the increasing number of customers using products and programs offered by Bank BJB Branch Office in Mojokerto.